PENGARUH DISIPLIN, KEPUASAN KERJA DAN MOTIVASI TERHADAP PRODUKTIVITAS KERJA PEGAWAI SEKRETARIAT DAERAH KOTA TANJUNGBALAI - Hurmaini Nasution; Evi Rahmwati; Three Indra Bakti; Alboin Adarian; Ajimi . (Jurnal Prodi Fakultas Ekonomi-UISU, 2021)
The formulation of the problem in this research is: Do discipline, job satisfaction and motivation affect the work productivity of employees at Sekretariat Daerah Kota Tanjungbalai. This study aims to determine the effect of job satisfaction and motivation on employee productivity. With total sampling technique, the sample in this study was 36 people. The results showed; Discipline partially has a positive effect on employee work productivity; Job satisfaction partially has a positive effect on employee work productivity; Motivation partially has a positive effect on employee work productivity; Discipline, job satisfaction and motivation have a positive and significant effect on employee work productivity.